First Description of mcr-1 -Mediated Colistin Resistance in Human Infections Caused by Escherichia coli in Latin America - Rapoport, Melina (2016)
Yi-Yun Liu and colleagues recently reported the emergence of plasmid-mediatedcolistin resistance in China, raising a great concern around the world (1-5). The mcr-1 gene was originally detected in commensal Escherichia coli from pigs, but immediately associated with other Enterobacteriaceae species from farm animals, meat, and human Origin (1-5). A previous study reported short-term intestinal colonization in travelers to South America, suggesting the presence of mcr-1 gene in the Region (4). In this manuscript, we describe the detection of mcr-1 in E. coli isolates causing human Infections in Argentina.